Glochidion zeylanicum leaf extracts exhibit lifespan extending and oxidative stress resistance properties in Caenorhabditis elegans via DAF-16/FoxO and SKN-1/Nrf-2 signaling pathways - Duangjan, Chatrawee; Wink, Michael (Phytomedicine, 2019)
Background - Glochidion zeylanicum (GZ), a common plant in Thailand and Eastern Asia, is rich in antioxidants. However, the possible anti-aging and oxidative stress resistance properties of GZ leaf extracts (hexane and methanol extracts) have not been reported. - Purpose - We aimed to provide the first science-based evidence of the beneficial effects of GZ on anti-aging and oxidative stress resistance in the Caenorhabditis elegans model. - Methods - The phytochemical composition of the hexane and methanol extracts were analyzed using GLC-MS and LC-MS. Fingerprinting analysis of the extract was performed by RP-HPLC. We determined total phenolics, flavonoids, and antioxidant properties via DPPH and ABTS assays. Oxidative stress resistance, anti-aging and lifespan were studied in C. elegans treated with leaf extracts. - Results - GZ leaf extracts protected the worms against oxidative stress and attenuated ROS accumulation. The expression of stress-response genes, such as SOD-3, and GST-4 were up-regulated, whereas HSP-16.2 was down-regulated after GZ treatment. The oxidative stress resistance properties of GZ possibly involved the DAF-16/FoxO and SKN-1/Nrf-2 transcription factors. GZ leaf extracts improved pharyngeal pumping function and autofluorescent pigment attenuation suggesting anti-aging properties. GZ leaf extracts modulated the lifespan extension in C. elegans. - Conclusion - This study reports novel anti-aging and antioxidant activities of GZ leaf extracts, suggesting a novel bioactivity for a medicinally important plant and supplementary drug against oxidative stress.